If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 4(1) Multiply 4 * 1 y = 4 Solving y = 4 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 4
| 4b^2=256 | | 4y-(2y-1)=7 | | x^2+2x-143=0 | | 9y-14=26+13y | | 3=x+3-x | | 5-(8-c)=0 | | 7x=109.2 | | y=12x+420 | | 260=k(1300) | | 2x=12.25 | | 48=k(6) | | 8m-(6m-3)=9 | | 3n-(5n+2)=8 | | 12h-18=12h-18 | | 6(y+2)-2y=15 | | 2x+19=1x-80 | | 6-(3x-3)-[2(-4x-1)]=(-3x+2) | | 12-2x=7x-15 | | 5n-9=2n+3 | | -(-4x+6-8)= | | -f(x-2)g=(x^2-3+2) | | 18=k(3) | | -24x+4x^2=0 | | (3x+72)(x-1)= | | 5x=x+26 | | 12h-18=(4h-6) | | 12x-60=0 | | 6(4y-1)=5 | | 2(x+5)=8 | | 3-n=33 | | x-6=(x-4)1/2 | | y=1.5(1) |